Application of multilayer finite elements of variable thickness in the calculation of reinforced concrete slabs in the "Prince" computer complex - K. R. Aidemirov; V. P. Agapov; G. M. Murtazaliev (Вестник Дагестанского государственного технического университета: Технические науки, 2021)
Objective. A family of multilayer finite elements designed for calculating reinforced concrete slabs and shells of variable thickness is described. The features of the formation of stiffness matrices associated with the variability of the cross-section of elements are considered.Methods. The family is based on the simplest planar triangular element constructed using the Kirchhoff hypothesis. The transverse displacements in this element are approximated by an incomplete cubic polynomial. This element is not suitable for practical use, but it is based on improved elements of three- and foursided shape in the plan. Special attention is paid to the consideration of cross-section variability.Results. The results of testing the developed elements are presented and the advantages of their use in the practice of design and calculation of structures are shown.Conclusion. The developed PRINCE software package can be useful in the design and calculation of structures containing plates of variable thicknesses.